Evaluation of the Implementation of Outpatient Electronic Medical Records at Arjosari Community Health Center, Pacitan - Sinta Novratilova; Elvina Yuan Mirna (Universitas Muhammadiyah Palembang, 2026)
ABSTRACT Puskesmas Arjosari Pacitan has developed electronic medical record documentation through the Puskesmas Management Information System and upgraded it into a web-based Electronic Medical Record system in June 2024. This study aimed to evaluate the implementation of Electronic Medical Records in outpatient services and identify supporting and inhibiting factors using the 5M approach, consisting of man, money, machine, method, and material. This research employed a descriptive qualitative method. The main informants were seven users of the system, including medical record officers, administrative staff, nurses, and an outpatient physician, while the head of the public health center served as a triangulation informant. Data were collected through interviews, observation, and documentation, then analyzed using data reduction, data display, conclusion drawing, and source triangulation. The findings showed that human resources and material aspects supported the implementation because staff understood the system workflow and the internet network was relatively stable. However, several barriers remained, including limited budget allocation, inadequate hardware availability, the absence of a detailed standard operating procedure, limited access to reporting features, and a suboptimal user interface. This study concludes that financial constraint is the most dominant barrier because it affects hardware procurement, staff training, and system development. Therefore, Puskesmas Arjosari needs dedicated budget planning, stronger technological infrastructure, a specific standard operating procedure, and improved coordination with the vendor to ensure effective and sustainable implementation.Keywords: Public Health Center, Electronic Medical Records, Outpatient Services, Implementation Evaluation, 5M Factors